Impact of Tocolytic Therapy on Cardiovascular Outcomes in Preterm Labor: A Systematic Review and Meta-Analysis - Ni Putu Ika Regiana Maharani; I Gede Agus Rio Saputra; Anak Agung Ngurah Gede Anggra Pramana; I Putu Gede Budiana (HM Publisher, 2025)
Background: Preterm labor is a significant cause of neonatal morbidity and mortality, and tocolytic therapy is often used to delay delivery and improve neonatal outcomes. However, tocolytic drugs can have adverse cardiovascular effects, including an increased risk of atrial fibrillation (AF). This meta-analysis aims to evaluate the impact of tocolytic therapy on cardiovascular outcomes in preterm labor, focusing on the risk of AF. Methods: A systematic literature review was conducted following PRISMA guidelines. Relevant studies published between 2013 and 2024 were identified through PubMed, Scopus, ScienceDirect, and Cochrane Library. Studies evaluating the cardiovascular effects of tocolytic therapy in preterm labor were included. The primary outcome was the incidence of AF. Secondary outcomes included other cardiovascular adverse events. Results: Ten studies met the inclusion criteria, comprising 550 pregnant women receiving tocolytic therapy. Tocolytic therapy was associated with a significantly increased risk of AF compared to no tocolytic therapy (mean difference 0.2, 95% CI 0.10-0.30). Nifedipine and ritodrine had a higher risk of AF compared to atosiban. The risk of AF was also higher in patients with pre-existing cardiovascular diseases. Conclusion: Tocolytic therapy, particularly with nifedipine and ritodrine, increases the risk of AF in preterm labor. Atosiban appears to be a safer option for patients with cardiovascular risk factors. Careful consideration of the potential cardiovascular risks and benefits is crucial when making tocolytic therapy decisions.